The Utilization of Vindes Social Media as a Visual Communication Case Study of Vindes Sport Content - Shabrina Maghfirah, Inez; Edhy Aruman, Ahmad (Jurnal Mamangan, 2024)
In recent years, there has been a rapid increase in the use of social media in Indonesia and the world. Vindes Media is a digital platform that seeks to provide informative and entertaining content, providing space for the young generation to empower their aspirations, collaborate with each other, and contribute to the creative, sports and arts industries. This research aims to provide insight into effective communication with audiences interested in the world of sports. This research uses qualitative methods by utilizing Harold D. Lasswell's communication theory which describes communication through the question "Who Says What in Which Channel to Whom with What Effect". The expected output of this research is to contribute to academic understanding regarding the effectiveness and impact of using Vindes Media social media in the context of visual communication in the field of sports. Vindes presents interesting visual communication content so that many audiences are engaged and loyal. The conclusion of this research is that Vindes in its social media provides a means of visual communication for the Vindes Sport campaign through various types of visual communication, especially infographics, photography and visual videos. The visual communication content presented was also very interesting and in accordance with the event theme. The implication of this research is that Vindes' frequency of posting visual communication content is also quite large, around four posts every day. So, these few factors lead to great engagement and interaction with the audience